Persepsi Masyarakat Mengenai Konsep Uang Hilang pada Pernikahan Adat Persatuan Keluarga Daerah Pariaman Kuamang Kuning - Tike Putriana; Yoan Mareta; Budi Purnomo (UIN Imam Bonjol Padang, 2024)
This research aims to determine the public's perception regarding the concept of lost money in traditional marriages in the Pariaman Kuamang Kuning Regional Family Association. The method used in this research is qualitative description. The steps used include observation, interviews, literature study and documentation. The results of this research contain the views of the family unity community in the Pariaman area regarding the concept of lost money. Lost money is a tradition carried out by the Pariaman people by giving a certain amount of money to the prospective groom which will later be used as kitchen money and the money will not be returned. and is the full right of men. Many people disagree with the concept of lost money, this is because there is an opinion that men seek to profit from lost money and harm women who must pay japuik money, lost money including customary money. However, quite a few people think that the concept of lost money has an important meaning in respecting men, where later men will become guests in women's families because the Pariaman community implements a matriennial system. Apart from that, lost money is also a form of pride in the family of women who have sons-in-law. with a high social level